2016
DOI: 10.1111/jace.14198
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Charge Transport in ZnO Nanocomposite Through Interface Control Using Multiwall Carbon Nanotubes

Abstract: Hybrid strategy of ZnO with carbon nanotube (CNT) has been attempted, and synergistic effects have been demonstrated in ZnO-CNT hybrid nanostructures owing to the advantageous effects of interface modification on the charge transport process. Here, we report the effects of interface control using multiwall CNTs (MWCNTs) on the charge transport properties in Al-doped ZnO (AZO) nanocomposite. Although the AZO-MWCNT nanocomposite is composed of numerous nanograins, it shows single crystalline charge transport beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Because there is no depletion layer among Bi 2 Te 3 grains and CNT, regarding the PEF nanocomposite film, CNT would increase the carrier mobility as carrier migration channels. [ 60 ] The PEF treatment decreases the carrier concentration while it increases the carrier mobility. In addition, this kind of nanocomposite film may have additional features because the nanocomposite substrate was prepared in the air environment.…”
Section: Results and Analysismentioning
confidence: 99%
“…Because there is no depletion layer among Bi 2 Te 3 grains and CNT, regarding the PEF nanocomposite film, CNT would increase the carrier mobility as carrier migration channels. [ 60 ] The PEF treatment decreases the carrier concentration while it increases the carrier mobility. In addition, this kind of nanocomposite film may have additional features because the nanocomposite substrate was prepared in the air environment.…”
Section: Results and Analysismentioning
confidence: 99%
“…These samples include three categories: (1) CNTs/ZnO composite powers synthesized by using commercial CNTs combined with ultrasonic dispersion (named as 2.0% CNTs/ZnO); (2) ZnO powders with 2.0 wt% Ni catalysts grown on the surface (named as 2.0% Ni/ZnO); and (3) ZnO powders with in-situ grown CNTs using different loading contents of Ni catalysts. It is shown that the main patterns of all samples can be indexed to the wurtzite structure of ZnO (PDF#36-1451)[40]. Sharp diffraction peaks of ZnO can be obviously seen in all samples, indicating good crystallinity.…”
mentioning
confidence: 93%